2014
DOI: 10.1097/npt.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Clinically Meaningful Difference in Gait Speed in Persons With Parkinson Disease

Abstract: Our data revealed that the clinically important difference in gait speed among persons with Parkinson disease on medication ranged from 0.05 m/s to 0.22 m/s by distribution-based analysis and ranged from 0.02 m/s to 0.18 m/s per level within the anchor-based metrics. These data will aid in evaluating the effectiveness of interventions to improve gait speed in persons with Parkinson disease.Video Abstract available. See video (Supplemental Digital Content 1, http://links.lww.com/JNPT/A77) for more insights from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
91
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 38 publications
10
91
3
2
Order By: Relevance
“…35 Minimal detectable change and clinically important differences, based on data distribution and effect size metrics, have only been established for on medication gait velocity in people with PD. 3639 On a group level, a 0.06 m/s improvement in on medication comfortable gait velocity has been associated with moderate clinically important difference in the UPDRS. 39 In the current study, the average improvement in both groups met or exceeded 0.06 m/s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Minimal detectable change and clinically important differences, based on data distribution and effect size metrics, have only been established for on medication gait velocity in people with PD. 3639 On a group level, a 0.06 m/s improvement in on medication comfortable gait velocity has been associated with moderate clinically important difference in the UPDRS. 39 In the current study, the average improvement in both groups met or exceeded 0.06 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…3639 On a group level, a 0.06 m/s improvement in on medication comfortable gait velocity has been associated with moderate clinically important difference in the UPDRS. 39 In the current study, the average improvement in both groups met or exceeded 0.06 m/s. 39 At an individual level, the minimal detectable change values for on medication gait velocity in people with PD, based on a 95% CI and measurement reliability are 0.09 m/s for comfortable gait velocity and 0.13 m/s for fast gait velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Even in this small sample, we detected substantial variability in activity and time in bed within and across participants, observed that passively measured gait speed at home is slower than the measurement in the clinic [16], and assessed and visually represented patterns of daily activity and sleep. Device-derived measures correlate well with typical PD measures and offer a number of advantages.…”
Section: Discussionmentioning
confidence: 99%
“…We think that our data are noteworthy for physicians, physiotherapists, and researchers. The walking speed of patients with Parkinson's disease has been shown to be related with age, disease severity, and balance in the literature (28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Many components of walking have caught the attention of physicians but walking speed is the most important of all (28) because independence in society correlates with walking speed; walking speed is considered as an important clinical marker. Walking speed is a reliable evaluation and can be used to determine the ability of walking in patients with Parkinson's disease (29). We used walking speed as a variable to compare the groups who had and had not fallen.…”
Section: Discussionmentioning
confidence: 99%